Toxicological evaluation of Sargassum polycystum in mice with loperamide-induced constipation - Chittipong Tipbunjong,; Tanaporn Hengpratom,; Saranya Peerakietkhajorn,; Jaruwan Mayakun,; Nawiya Huipao,; Pissared Khuituan,; Piyaporn Surinlert,; Chumpol Pholpramool, (Penerbit Universiti Kebangsaan Malaysia, 2024)
Constipation gradually increases in people after the age of 50 years leading to difficulty in stool passage. Until now, there have been no effective drugs without side effects. This study investigated the preventive potential and toxicity of Sargassum polycystum extract (SPE) against loperamide-induced constipation in mice. Daily oral administration of SPE (100, 500 and 1000 mg/kg) for 14 days significantly increased defecation frequency in constipation mice. Additionally, no significant differences in blood haematological and biochemical indices between the control, constipation and SPE-treated groups were detected. Histopathological examinations revealed non-toxic effects in liver, kidney and colon tissue samples from the SPE-treated groups compared with the control and constipation groups. Real-time polymerase chain reaction showed that the administration of SPE significantly modulated Saa3, Odc1 and Clu expressions that promote the health of living organisms compared with the control group. Overall, this study showed that daily oral administration of Sargassum polycystum for 14 days could prevent constipation without any adverse effects. Sargassum polycystum is suitable for further use as a supplement or drug to manage constipation.